Intra- and Inter-species Wood Anatomical Variation in Balau Group of Shorea of Malay Peninsula - Pande, P. K.; Negi, Krishna; Singh, Magan (Indian Forester, 2005)
The paper deals with the intra- and inter-species variation in the different wood elements of Balau group of Malay Shorea. Variance ratio test indicated that variations in the wood elements viz. fibre length, vessel element diameter and wall thickness are significant between species. These variations are non-significant between samples of same species (α = 0.05). Mean minimum and maximum fibre-, vessel element-length, diameter, wall-thickness were recorded as 954 ± 139μm (S. tumbuggaia) - 1360 ± 139 μm (S. exelliptica), 351 ± 46μm (S. obtusa) - 45l±119 μm in S. atrinervosa (mean 403 ± 70.6), 113 ± 35 (S. obtusa) - 223 ± 34μm (S. submontata) and 4μm (S. lumutensis) - 8.1 ±m (S. atrinervosa), respectively. Minimum density was recorded for S. meadiana (730 kg m-2) while maximum recorded for S. laevis (1049 kg m-2). Dimensions of wood elements are also correlated to each other for few characters. Wall thickness and fibre diameter and density and vessel element length are positively correlated (α=0.05). Cluster analysis was done for the 18 species of Balau group on the basis of wood anatomical characters viz. fibre-length, diameter, vessel member-length, diameter, wall thickness and specific gravity. Two clusters are formed at 25 inter-cluster distance.S. guiso, S. ochrophloia, S. meadiana, S. Sumatrana, S. ciliata, S. laevis, S. glauca, S. materia lis, S. exelliptica, S. atrinervosa, S. obtusa form first cluster while S. collina, S. lumutensis, S. maxwelliana, S. foxworthyi, S. robusta. Submontana and S. tumbuggaia form the second cluster S. obtusa was separated from first cluster at 15 inter-cluster distance while S. tumbuggaia separated at 10 inter-cluster distance from the second cluster.